Severe Acute Respiratory Syndrome Coronavirus 2 Diagnostic Tests for Border Screening During the Very Early Phase of Coronavirus Disease 2019 Pandemic: A Systematic Review and Meta-Analysis - Chua, Pearleen Ee Yong; Gwee, Sylvia Xiao Wei; Wang, Min Xian; Gui, Hao; Pang, Junxiong (Frontiers in Medicine, 2022)
Diagnosis of SARS-CoV-2 during border screening among returning residents and prioritized travelers during the early phase of pandemic can reduce risk of importation and transmission in the community. This study aimed to compare the accuracy of various SARS-CoV-2 diagnostics and assess their potential utility as border screening for infection and immunity. Systematic literature searches were conducted in six electronic databases for studies reporting SARS-CoV-2 diagnostics (up to 30 April 2020). Meta-analysis and methodological assessment were conducted for all included studies. Performance of diagnostic tests was evaluated with pooled sensitivity, specificity and their respective 95% confidence intervals. 5,416 unique studies were identified and 95 studies (at least 29,785 patients/samples) were included. Nucleic acid amplification tests (NAAT) consistently outperformed all other diagnostic methods regardless of selected viral genes with pooled sensitivity of 98% and pooled specificity of 99%. Point-of-care (POC) serology tests had moderately high pooled sensitivity (69%), albeit lower than laboratory-based serology tests (89%), but both had high pooled specificity (96-98%). Serology tests were more sensitive for sampling collected at ≥7 days than ≤7 days from the disease symptoms onset. POC NAAT and POC serology tests are suitable for detecting infection and immunity against the virus, respectively as border screening. Independent validation in each country is highly encouraged with the preferred choice of diagnostic tool/s.